Implementation of the Death Penalty in the Perspective of Human Rights in Indonesia - Sina, La (Hasanuddin Law Review, 2016)
The 1945 Constitution of Indonesia provides for rights to life and to remain free from torture that are fundamental human rights that shall not be curtailed under any circumstance. Since 1945, Indonesia does not regulate the protection of the right of life to the citizens. Until 1946, enacted Law No. 1 of 1946 concerning the Indonesian Criminal Code which in several provisions concerning the death penalty. Death sentences and executions in Indonesia is always debatable. However, it is still implemented and can not be avoided, unless the change of its legal provisions. This study was a normative research or doctrinal research. The results of the study shows that the provisions of death penalty in Indonesia is still enforced because have been regulated in the Criminal Code and several organic laws such as the law of terrorism, narcotics, corruption, and human rights justice. The death penalty is contrary to Article 28I of the 1945 Constitution. It has set the rights to life, so that no one may violate human rights, including the government and the country is not granted the right to revoke rights for every citizen. The Indonesian government should not impose the death penalty contained in the draft new Code, and abolish the death penalty in its organic law that had been imposed on the offenders. Preferably, the death penalty may be replaced by alternative punishment with life imprisonment, a prison within a specified time or according to the judge’s decision.